Giving cash to the poor: A study of Pantawid Pamilya cash grants generosity, frequency, and modality - Kris Ann M. Melad; Nina Victoria V. Araos; Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2020)
This study assesses the payment system of the Pantawid Pamilyang Pilipino Program (4Ps or Pantawid Pamilya) in terms of the amount, frequency, and mode of payment delivery of the cash transfers. The study is an early attempt of the Institute to examine the Pantawid Pamilya implementation and recommend improvements in its payment system in light of the enactment of RA 11310 which institutionalized the program and identified PIDS to conduct regular assessments on the program's implementation and impact. The underlying framework for the study is based on the idea that the amount of cash grants and its delivery system should be able to encourage desired behaviors among beneficiaries and help achieve the program's target outcomes. The study answers the research objectives using a combination of qualitative and quantitative methods of analysis that include a review of the available literature on payment systems of international CCTs; re-assessment of the cash grant values in relation to original intended levels and devaluation due to inflation; assessment of the implementation of the payment system including challenges, facilitating factors, and alternative ideas; and an assessment of the impact of the design features of the payment system on select outcome variables. The study uses administrative data of the Department of Social Welfare and Development (DSWD), survey data from the program's 3rd impact evaluation, interviews of key program implementers in the payment system, focus group discussions with beneficiaries, and an online survey focused on the payment delivery aspect of the Social Amelioration Program (SAP) among Pantawid Pamilya beneficiaries. The results show that the program needs to be more responsive in adjusting the benefit level of the cash grants vis-à-vis inflation and threats to welfare of the beneficiaries. With regard to payment frequency, there is no strong demand by the beneficiaries for more frequent payouts. Changes in frequency of payment should also be carefully examined to know if benefits outweigh additional costs in the operations. Although the payment delivery system has improved through the years primarily due to the conversion of mode of payment to cash cards, some opportunities to improve the payment delivery of the program are still present. Finally, the experience with the SAP distribution demonstrated the ease and speed of distributing assistance in times of emergencies when recipients (e.g., 4Ps beneficiaries) are identified and a payment system in place.
Keywords: 330; Pantawid Pamilya; Conditional Cash Transfer; cash grants; payment system